Een dakloos gedenkteken voor Michiel de Ruyter - Doedens, Jaap (Acta Neerlandica, 2026)
Almost unbeknownst to virtually anyone, the fragments of a monument commemoratingthe liberation of galley slaves by Michiel de Ruyter lay for years in the parking garage ofthe Reformed Theological Seminary in Pápa. Originally, this memorial stood in thecourtyard of the military academy, the Zrínyi Miklós Nemzetvédelmi Egyetem (MiklósZrínyi Defense University) on Üllői Street in Budapest. It was erected in 2002 to commemorate the liberation of the Hungarian ministers who had been sentenced to the galleysand were freed by Michiel de Ruyter in Naples in 1676. The monument was designed andcreated by Colonel Dr. Lajos Berek, who was also the rector of that university. When thismilitary academy moved to the campus on the Hungária ring road in 2008, the old buildingwas sold. The monument was taken down. The Bolyai János Honvéd Alapítvány (JánosBolyai Defense Foundation) donated the memorial to the Protestáns Tábori Püspökség(Protestant Military Diocese). The new owner would look for a new location for the statue.Since there was no place to put it up again at that time, they looked for a place where itcould be stored “temporarily.” That place was the parking garage of the ReformedTheological Seminary in Pápa.